Studi Evaluasi Sistem Informasi Geografi Kasus Stunting Menggunakan COBIT 5 Framework - I Gede Wiryawan; Dony Setiawan Hendyca Putra; Estin Roso Pristiwaningsih; Ely Mulyadi; Prawidya Destarianto; Khafidurrohman Agustianto (Universitas Diponegoro, 2022)
An application for data collection of stunting cases has been developed with data visualization in digital maps. This detailed information about stunting is a solution offered to solve problems in areas prone to stunting. This system requires further testing to get feedback from several relevant stakeholders. The COBIT 5 framework, with a combination of DSS and MEA domains, is used in this study to test this geography-based system of stunting cases. The interviews with system administrator respondents showed that the lowest scores were in the DSS05 and MEA02 domains of 75.20 and 74.67 on the Linkert scale. The same results were also obtained from management respondents consisting of heads of Puskesmas and midwives, 77.54 and 75.95. In the end, the level of achievement of the domain of the current system and its monitoring is compared between the current condition (as-is) and the general condition (to-be), indicating a gap. Based on the gap analysis, two-gap values were obtained in the DSS05 and MEA02 domains. Recommendations for improvement in the future are in terms of vulnerability to errors and increasing the ability of internal parties to control the system to handle errors.